HUBUNGAN ANTARA TIPE KEPRIPADIAN DENGAN SIKAP TERHADAP KETERAMPILAN BERKOMUNIKASI PADA MAHASISWA KEDOKTERAN - Bension, Johan Bruiyf; Huwae, Laura Bianca Sylvia; Maruanaya, Samuel; Noija, Stazia (Ensiklopedia of Journal, 2025)
Abstract: Communication skills are one of the essential soft skills that doctors must have in building effective relationships with patients. Attitude towards communication skills is influenced by various factors, one of which is the individual's personality type. This study aims to determine the relationship between personality type and attitude towards communication skills in Pattimura University Faculty of Medicine students. This study used a cross-sectional analytic design with a sample size of 399 students from semester 2, 4, 6, and 8 selected using total sampling technique. The instruments used included the Myers-Briggs Type Indicator (MBTI) to identify personality types and the Indonesian version of the Communication Skills Attitudes Scale (CSAS) to measure attitudes towards communication skills. The results showed variations in the relationship between personality type and attitudes towards communication skills. Furthermore, the results of this study are expected to be a source of information and evaluation material in designing communication skills learning strategies that are more effective and in accordance with the characteristics of students, as well as contributing to the development of medical education. Keywords: personality type, communication skills, medical students, MBTI, CSAS